Pengaruh Project Based Learning dan Minat Kewirausahaan Terhadap Hasil Belajar Biologi - Nurafifah, Syifa; Firdaus, Deden Iqbal; Patimah, Pepi; Susilawati, Wati; Karjadinata, Rahayu; Chusni, Minan (MUNAQASYAH : Jurnal Ilmu Pendidikan dan Pembelajaran, 2024)
Instilling an entrepreneurial spirit and long-term investment in providing cognitive knowledge, competencies and encouraging students to be able to take advantage of opportunities so that they are able to face global competition in the industrial revolution 4.0. The purpose of this study was to see the effect of project based learning and entrepreneurial interest on biology learning outcomes. This research is a quasi-experimental research (Quasi Experiment). The experimental design used in this study is the One Shot Case Study. The sample data selected for the experimental class is only one class, namely class 12 IPS 2, totaling 30 people. The sample determination of this study was carried out by Random sampling technique is random.This is because according to the results of observations in the field the ability of students in learning outcomes is classified as the same and there is no superior class.The data in this study consist of student project assessment data taken from student project assessments, entrepreneurial interest is taken from the distribution of questionnaires consists of several indicators of entrepreneurial interest, and learning outcomes are taken from multiple choice test data as many as 20 questions in the form of multiple choice Post tests after learning is carried out. Judging from the results of the research, it can be concluded that the project value and students' entrepreneurial interest only have less influence and the rest more influenced by other things outside the research. Based on the F test, the significance value is obtained that there is a relationship between project value and interest in entrepreneurship together with student learning outcomes. With the existence of project-based learning research and entrepreneurial interest in biology learning outcomes, it is hoped that there will be an increase in student interest in entrepreneurship.